The perceived impact of agricultural advice in Ethiopia. Issue 2 (15th March 2017) - Hamilton, Alexander; Hudson, John
ABSTRACT: Purpose: We examine the impact of advice given by extension agents to Ethiopian farmers, as perceived by the farmers themselves. Design/methodology/approach: Using survey data from 2014, we analyze the perceived impact of advice on farmers' incomes and crop yields. We use a bootstrapped instrumental variable (IV) estimator and the conditional mixed process estimator. Theoretical implications: The impact of advice will depend upon its relevance and whether and how efficiently it is implemented by the farmer. This in part depends upon the farmer's ability and on the impact of fully implemented advice on output, which will vary from farm to farm. Findings: There is a positive perceived impact of most advice on both crop yields and income. However, some advice works better in drought-affected areas and other in non-drought-affected areas. Fertilizers have more impact on crop yields than income, possibly reflecting cost factors. There is evidence that the farmers' ability to implement the advice increases with their level of education and that advice is being tailored to the needs of the individual. Practical implications: Advice has a positive impact on both crop yields and income. However, not all advice is equally effective and effectiveness varies according to farmer and farm characteristics. There is little evidence of credit advice having a positive impact. Originality/value: The paper is one of only a few to analyze farmers' perceptions of advice impact and, as far as we are aware, is the first to analyze how advice effectiveness varies according to farmer and farm characteristics.